Azido Functionalized Nucleosides Linked to Controlled Pore Glass as Suitable Starting Materials for Oligonucleotide Synthesis by the Phosphoramidite Approach. Issue 46 (25th November 2021) - Müggenburg, Frederik; Biallas, Alexander; Debiais, Mégane; Smietana, Michael; Müller, Sabine
Abstract: It has long been debated whether easily reducible azide groups can withstand the conditions of oligonucleotide synthesis by phosphoramidite chemistry. We have synthesized various 2′‐ and 3′‐azido modified nucleosides and immobilized them on controlled pore glass (CPG) to be used as starting material for the synthesis of oligonucleotides (ONs) with 3′‐terminal azide (attached to C2′ or C3′). In a model study, immobilized 3′‐azidoadenosine was used as a starting block for the synthesis of a series of oligodeoxynucleotides (ODNs) of increasing length. Upon synthesis, the ODNs were enzymatically digested into monomers and analyzed by RP‐HPLC. A peak corresponding to 3′‐azidoadenosine was clearly identified in all samples. Quantitative analysis showed that 3′‐azidoadenosine was present in nearly the expected ratio to deoxycytidine, which was used as an internal standard. Most importantly, the ratio remained the same for all three ODNs regardless of their length, demonstrating that a higher number of coupling cycles does not lead to higher degradation of the azide. Thus, 2′‐ or 3′‐azido nucleosides attached to a solid support are excellent starting materials for the synthesis of oligonucleotides with 3′‐terminal azide. Abstract : Azido modified nucleosides are powerful tools for the modification of oligonucleotides (ONs). However, azido moieties can react unfavorably when exposed to phosphoramidites, which are the standard building blocks in chemical ON synthesis. In this work, synthetic approaches for three azido modified nucleosides as well as investigations regarding the general stability of the azide function during chemical oligonucleotide synthesis are reported.